Recent Advances in Transition-Metal-Free (4+3)-Annulations - Lam, Heather; Abel-Snape, Xavier; Köllen, Martin F.; Lautens, Mark (Synthesis, 2021)
(4+3)-Annulations are incredibly versatile reactions which combine a 4-atom synthon and a 3-atom synthon to form both 7-membered carbocycles as well as heterocycles. We have previously reviewed transition-metal-catalyzed (4+3)-annulations. In this review, we will cover examples involving bases, NHCs, phosphines, Lewis and Brønsted acids as well as some rare examples of boronic acid catalysis and photocatalysis. In analogy to our previous review, we exclude annulations involving cyclic dienes like furan, pyrrole, cyclohexadiene or cyclopentadiene, as Chiu, Harmata, Fernándes and others have recently published reviews encompassing such substrates. We will however discuss the recent additions (2010–2020) to the literature on (4+3)-annulations involving other types of 4-atom-synthons.1 Introduction2 Bases3 Annulations Using N-Heterocyclic Carbenes3.1 N-Heterocyclic Carbenes (NHCs)3.2 N-Heterocyclic Carbenes and Base Dual-Activation4 Phosphines5 Acids5.1 Lewis Acids5.2 Brønsted Acids6 Boronic Acid Catalysis and Photocatalysis7 Conclusion
Keywords: annulation; (4+3)-annulations; organocatalysis; Lewis acids; Brønsted acids; phosphines; N-heterocyclic carbenes